Time of Test, Era of Opportunity - Nations Unies (United Nations, 2016)
This publication features a selection of speeches delivered by the United Nations Secretary-General Ban Ki-moon during his tenure from 2006 to 2016, a decade that has witnessed considerable upheaval and transformation. The most important issues of our time are addressed in this volume, ranging from international peace and security to sustainable development, climate change to disarmament, humanitarian action to human rights, justice and the rule of law, and the empowerment of women and girls and of the new generations. This collection of speeches provides vital insights into our rapidly changing world and of the multiple challenges facing humanity today.